The critical thinking-oriented adaptations of problem-based learning models: a systematic review - Yu, Ling; Zin, Zuhana Mohamed (Frontiers in Education, 2023)
Critical thinking is a significant 21st-century skill that is prioritized by higher education. Problem-based learning is becoming widely accepted as an effective way to enhance critical thinking. However, as the results of studies that use PBL to develop CT have had mixed success, PBL models need to be modified to guarantee positive outcomes. This study is a systematic review that analyzed how studies have adapted Problem-Based Learning (PBL) to become more Critical Thinking (CT)-oriented, evaluated the effectiveness of these adaptations, and determined why certain adaptations were successful. The review was conducted in accordance with PRISMA(Preferred Reporting Items for Systematic Reviews and Meta-Analyses) by searching the scientific databases Scopus and Web of Science. Twenty journal articles were chosen based on their adherence to the inclusion criteria established by PICo (Population, Phenomenon of Interest, and Context). In these studies, PBL adaptations were categorized into five classifications, with activities centred on CT development being the most prevalent approach. Researchers utilized a variety of analytical methodologies to assess the effectiveness of these adaptations and derive significant insights and formulate valid conclusions. An analysis of all selected studies revealed positive outcomes, indicating that incorporating CT elements into PBL was effective in enhancing students’ CT. These findings were categorized into nine factors that contribute to the successful adaptation of PBL to be CT-oriented.